Animasi 2D Penjelasan dan Penanganan Virus & Bakteri Menggunakan Animate CC Dengan Teknik Motion Tween Berbasis Multimedia - Surya Tjahyadi; Dalwin Christopher (Journal of Information System and Technology (JOINT), 2022)
2D Interactive Multimedia Animation is a guide for various media such as images, videos, sounds, and texts to be used as learning media that can attract learning interest from the users themselves. The animation is made in the form of interactive media in the form of .app/.apk format that can be used by users to obtain information in a visually interactive way. In the Interactive Multimedia, various kinds of information are available about viruses and bacteria as well as ways to handle them, designing 2D animation using the MDLC (Multimedia Development Life Cycle) method and using the Adobe Animate CC 2018 application, which is an advanced application from the previous Adobe Flash. The animation design itself also uses the Motion Tween technique available in the application, the results of the project are disseminated on social media such as whatsapp, line, instagram and youtube via the google drive link and demo results from the interactive multimedia are also available which are distributed on youtube. The results of the feedback from interactive multimedia, the first question has 14 positive 1 negative answers, the second question has 13 positive 2 negative answers, the third question has 13 positive 2 negative answers, the fourth question has 12 positive 3 negative answers, and the last question has suggestions and criticisms which end in the result of positive review from users.